Usability design of embodied conversational agents on handheld devices - Simmons, Carl Benjamin (The University of Edinburgh, 2014)
Embodied Conversational Agents (ECAs) potentially represent a way to deliver services to the public that would previously have require human staff. Making an ECA available online allows out-of-hours access to information and services, as well as allowing users to access the information anywhere there is an internet connection. As handheld devices grow in popularity and become the primary source of internet connection for many users, it is necessary to examine whether an ECA is appropriate for use on a handheld device, and what factors affect its usability. Over the course of four experiments this research examines how using a handheld device is different from using a PC, how an ECA should be presented on a handheld device, how using an ECA service in a public space affects the experience, and how an ECA should interact with users. It was determined that the usability of an ECA service is not affected by the device on which it is experienced, that on smaller screens or in demanding environments the ECA should be emphasised, and that text should be included in an ECA service as long as the ECA remains intermittently visible. It was also found that usability results from the laboratory can be generalised to the real world, that ECA services are appropriate for all ages and genders, that incorporating disclosure elements into an ECA service is a beneficial feature, and that while financial topics are appropriate to be discussed with an ECA, they are best kept to general rather than personal information. The following chapters present the necessary literary background to the field, before covering each experiment individually, and finally presenting detailed conclusions about the usability of ECAs on handheld devices.
Keywords: embodied conversational agents; ECAs; handheld devices; usability